Adherence to guideline recommendations in the management of pediatric cardiac arrest: a multicentre observational simulation-based study. (29th March 2022) - Corazza, Francesco; Stritoni, Valentina; Martinolli, Francesco; Daverio, Marco; Binotti, Marco; Genoni, Giulia; Ingrassia, Pier Luigi; De Luca, Marco; Palmas, Giordano; Maccora, Ilaria; Frigo, Anna Chiara; Da Dalt, Liviana; et al.
Abstract : Background and importance: Pediatric cardiac arrest is a rare emergency with associated high mortality. Its management is challenging and deviations from guidelines can affect clinical outcomes. Objectives: To evaluate the adherence to guideline recommendations in the management of a pediatric cardiac arrest scenario by teams of pediatric residents. Secondarily, the association between the use of the Pediatric Advanced Life Support-2015 (PALS-2015) pocket card, and the teams' adherence to international guidelines, were explored. Design, settings and participants: Multicentre observational simulation-based study at three Italian University Hospitals in 2018, including PALS-2015 certified pediatric residents in their 3rd–5th year of residency program, divided in teams of three. Intervention or exposure: Each team conducted a standard nonshockable pediatric cardiac arrest scenario and independently decided whether to use the PALS-2015 pocket card. Outcome measure and analysis: The primary outcome was the overall number and frequency of individual deviations from the PALS-2015 guidelines, measured by the novel c-DEV15plus score (range 0–15). Secondarily, the performance on the validated Clinical Performance Tool for asystole scenarios, the time to perform resuscitation tasks and cardiopulmonary resuscitation (CPR) quality metrics were compared between the teams that used and did not use the PALS-2015 pocket card. Main results: Twenty-seven teams (81 residents) were included. Overall, the median number of deviations per scenario was 7 out of 15 [interquartile range (IQR), 6–8]. The most frequent deviations were delays in positioning of a CPR board (92.6%), calling for adrenaline (92.6%), calling for help (88.9%) and incorrect/delayed administration of adrenaline (88.9%). The median Clinical Performance Tool score was 9 out of 13 (IQR, 7–10). The comparison between teams that used ( n  = 13) and did not use ( n  = 14) the PALS-2015 pocket card showed only significantly higher Clinical Performance Tool scores in the former group [9 (IQR 9–10) vs. 7 (IQR 6–8); P  = 0.002]. Conclusions: Deviations from guidelines, although measured by means of a nonvalidated tool, were frequent in the management of a pediatric cardiac arrest scenario by pediatric residents. The use of the PALS-2015 pocket card was associated with better Clinical Performance Tool scores but was not associated with less deviations or shorter times to resuscitation tasks.